ANALISIS PENGARUH KEPATUHAN WAJIB PAJAK PBB - Florentina Titus Purwaningsih; Arif Nugroho Rachman (STIE Trisna Negara OKU Timur, 2022)
The purpose of this study is to find out about tax knowledge, income levels, tax sanctions and tax services on taxpayer compliance with Land and Building Tax in Jumapolo District. The regression model used in this study is a multiple linear regression model with the help of SPSS. Sampling technique using random sampling method (random) obtained as many as 100 taxpayer respondents who have the obligation to pay Land and Building Tax in Jumapolo District. The results of the study partially show that tax knowledge, income levels, and tax sanctions have a significant effect on taxpayer compliance with Land and Building Tax. Meanwhile, tax services partially have no effect on taxpayer compliance with the Land and Building Tax.